2017
DOI: 10.2174/1871524916666160504104624
|View full text |Cite
|
Sign up to set email alerts
|

Stimulated CB1 Cannabinoid Receptor Inducing Ischemic Tolerance and Protecting Neuron from Cerebral Ischemia

Abstract: CB1R played an important part via several signaling pathways in the protection from ischemic stroke and in ischemic tolerance. The involved molecular signaling pathways include ERK1/2, PI3K/Akt/GSK-3β and the translocation and activation of PKCε. With the intimate association between CB1R and neuron injuries, to target the receptor will exert neuroprotective effects on cerebral ischemia, which provides wide foreground for a novel therapy target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“… 25 ESC takes a significant role via several downstream signaling pathways in ischemic tolerance and protection from ischemic stroke. 53 CB1R activation is one prime underlying mechanism, it can be mediated by URB597, as has been substantiated. 54 URB597 increases CB1R-mediated neuronal survival and neurotransmission, meanwhile up-regulating the levels of BDNF expression in the brain.…”
Section: Discussionmentioning
confidence: 78%
“… 25 ESC takes a significant role via several downstream signaling pathways in ischemic tolerance and protection from ischemic stroke. 53 CB1R activation is one prime underlying mechanism, it can be mediated by URB597, as has been substantiated. 54 URB597 increases CB1R-mediated neuronal survival and neurotransmission, meanwhile up-regulating the levels of BDNF expression in the brain.…”
Section: Discussionmentioning
confidence: 78%
“…Lipid peroxidation is a free-radical-mediated chain of reactions that, once initiated, results in an oxidative deterioration of polyunsaturated lipids, the components of biological membranes. There are controversial reports about the relationship between the CB1 endocannabinoid system and oxidative stress [48][49][50][51][52]. According to Mukhopadhyay et al [49], CB1 activation may amplify the reactive oxygen/nitrogen species-MAPK activation-cell death pathway by excessive inflammation and/or oxidative/nitrosative stress, which may contribute to the pathophysiology of cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…According to Mukhopadhyay et al [49], CB1 activation may amplify the reactive oxygen/nitrogen species-MAPK activation-cell death pathway by excessive inflammation and/or oxidative/nitrosative stress, which may contribute to the pathophysiology of cardiovascular diseases. Zhuang et al [52] demonstrated that CB1 is likely to provide an appropriate antioxidant balance by increasing endogenous free radical scavengers for neuroprotection.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of Akt can control multiple intracellular signals, such as the mTOR signaling pathway, GSK-3β signaling pathway etc. Then, the downstream signaling pathways can promote proliferation and survival after cerebral ischemia ( 48 50 ). In addition, some studies reported that treatment with IGF-1 after an ischemic stroke partially improved the ischemic damage of neurons induced by ischemia-reperfusion injury ( 51 , 52 ).…”
Section: Discussionmentioning
confidence: 99%